2022
DOI: 10.1111/acel.13569
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging mitochondrial hydrogen peroxide by peroxiredoxin 3 overexpression attenuates contractile dysfunction and muscle atrophy in a murine model of accelerated sarcopenia

Abstract: Age‐related muscle atrophy and weakness, or sarcopenia, are significant contributors to compromised health and quality of life in the elderly. While the mechanisms driving this pathology are not fully defined, reactive oxygen species, neuromuscular junction (NMJ) disruption, and loss of innervation are important risk factors. The goal of this study is to determine the impact of mitochondrial hydrogen peroxide on neurogenic atrophy and contractile dysfunction. Mice with muscle‐specific overexpression of the mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…The expression level of MondoA decreases with age that drives cellular senescence by impaired mitochondrial homeostasis through the expression of PRX3 [ 86 ]. In agreement with this finding, muscle-specific overexpression of PRX3 can attenuate contractile dysfunction and muscle atrophy in a SOD1 KO mouse model of accelerated sarcopenia by improving mitochondrial function [ 71 ].…”
Section: Roles Of Peroxiredoxins In Agingsupporting
confidence: 53%
“…The expression level of MondoA decreases with age that drives cellular senescence by impaired mitochondrial homeostasis through the expression of PRX3 [ 86 ]. In agreement with this finding, muscle-specific overexpression of PRX3 can attenuate contractile dysfunction and muscle atrophy in a SOD1 KO mouse model of accelerated sarcopenia by improving mitochondrial function [ 71 ].…”
Section: Roles Of Peroxiredoxins In Agingsupporting
confidence: 53%
“…Elevated muscle levels of these mitochondrial H 2 O 2 scavengers did not protect muscle mass in a 7-day sciatic nerve transection model, which may be because oxidized lipid and oxylipin levels were not impacted by these interventions. In contrast, elevated levels of Prdx3 and mitochondrial targeted catalase were protective in mitigating muscle loss in the CuZnSOD knockout mouse model (Sod1KO) of accelerated sarcopenia and frailty [ 51 , 52 ]. In the case of overexpression of muscle mitochondrial targeted catalase, the neuromuscular junction (NMJ) disruption seen in the Sod1KO mice was completely prevented preserving muscle mass and contractile function in the Sod1KO mice [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of overexpression of muscle mitochondrial targeted catalase, the neuromuscular junction (NMJ) disruption seen in the Sod1KO mice was completely prevented preserving muscle mass and contractile function in the Sod1KO mice [ 51 ]. However, overexpression of PRDX3 did not protect the NMJ; however, there still was a protection in muscle mass and force [ 52 ]. There is evidence that supports that PRDX3 may directly reduce lipid peroxidation in liver tissue (reduced F 2 isoprostanes and 4-HNE adducts) [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we asked whether cellular Ca 2+ homeostasis was disturbed in muscle from these two models and whether there was an impact on mitochondrial Ca 2+ metabolism or respiration. To test this, we challenged the mitochondrial CRC in isolated mitochondria from muscles in all three groups as previously described ( 4 , 27 ). We observed a significant decrease in CRC in mitochondria from both Sod1 KO and aging muscles compared to WT muscles, indicating a significant impairment in mitochondrial Ca 2+ buffering capacity, which is similar to what Picard et al ( 52 ) reported in aging muscles from rats.…”
Section: Discussionmentioning
confidence: 99%